Alteration of Homeostasis in Pre-osteoclasts Induced by Aggregatibacter actinomycetemcomitans CDT - Kawamoto, Dione; Ando-Suguimoto, Ellen S.; Bueno-Silva, Bruno; DiRienzo, Joseph M.; Mayer, Marcia P. A. (Frontiers in Cellular and Infection Microbiology, 2016)
The dysbiotic microbiota associated with aggressive periodontitis includes Aggregatibacter actinomycetemcomitans, the only oral species known to produce a cytolethal distending toxin (AaCDT). Give that CDT alters the cytokine profile in monocytic cells, we aimed to test the hypothesis that CDT plays a role in bone homeostasis by affecting the differentiation of precursor cells into osteoclasts. Recombinant AaCDT was added to murine bone marrow monocytes (BMMC) in the presence or absence of RANKL and the cell viability and cytokine profile of osteoclast precursor cells were determined. Multinucleated TRAP+ cell numbers, and relative transcription of genes related to osteoclastogenesis were also evaluated. The addition of AaCDT did not lead to loss in cell viability but promoted an increase in the average number of TRAP+ cells with 1-2 nuclei in the absence or presence of RANKL (Tukey, p < 0.05). This increase was also observed for TRAP+ cells with ≥3nuclei, although this difference was not significant. Levels of TGF-β, TNF-α, and IL-6, in the supernatant fraction of cells, were higher when in AaCDT exposed cells, whereas levels of IL-1β and IL-10 were lower than controls under the same conditions. After interaction with AaCDT, transcription of the rank (encoding the receptor RANK), nfatc1 (transcription factor), and ctpK (encoding cathepsin K) genes was downregulated in pre-osteoclastic cells. The data indicated that despite the presence of RANKL and M-CSF, AaCDT may inhibit osteoclast differentiation by altering cytokine profiles and repressing transcription of genes involved in osteoclastogenesis. Therefore, the CDT may impair host defense mechanisms in periodontitis.